(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-10-20 The essence of the conceptual and figurative concept in linguistic and literary approach is studied. The conceptual-figurative concept is one of the units that fill the figurative-semantic system of the author. Its function in an autobiographical work is considered as a way of transmitting the author’s consciousness, which is an organizing center that has a multi-level structure and a complex content of an artistic work. The role of the conceptual and figurative concept in the formation of the semantic center of the work is determined. The conceptual-figurative concept in an artistic autobiographical text is understood as a verbalized value-significant mental unit of an individual author’s picture of the world. The unit under study is considered from two points of view: as a generally accepted knowledge and as a reflection of the author’s subjective experience of experiencing reality. Key words: image, concept, conceptual and figurative concept, figurative semantic system, author’s consciousness, autobiographical work